Effects of carbon sources on production and properties of curdlan using Agrobaterium sp. DH-2. Issue 9 (1st October 2020) - Wan, Jie; Wang, Yifeng; Jiang, Deming; Gao, Hongliang; Yang, Guang; Yang, Xuexia
Abstract: Curdlan has wide potential application in the food and biomedical fields due to its unique thermal gel and biological activity. This study investigated the effect of six sugars including glucose, fructose, lactose, maltose, sucrose and xylose as carbon sources on production and properties of curdlan using Agrobacterium sp. DH-2. The maximum production (38.1 g/L and 37.4 g/L, respectively) and yield (0.58 g curdlan/g sucrose and 0.53 g curdlan/g maltose, respectively) of curdlan were achieved by sucrose and maltose, followed by glucose, fructose, lactose and xylose. Scanning electron micrographs showed that the surface of cells was smooth in strain growth phase, while cells were covered by curdlan matrix acted as a net in the curdlan synthesis phase. The highest glucosyltransferase activity (19.9 U/g biomass) corresponded to the maximum curdlan production using the sucrose medium. The molecular weight and gel strength of curdlan were influenced by the carbon sources. The curdlan from xylose medium resulted in a maximum molecular weight of 1.59 × 10 6  Da and the highest gel strength of 989.2 g/cm 2, while the curdlan from sucrose medium resulted in a lowest molecular weight of 1.10 × 10 6  Da and gel strength of 672.8 g/cm 2 . The high molecular weight of curdlan had high gel strength.